PENGARUH GAYA KEPEMIMPINAN DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA PEGAWAI PUSAT PEMBERITAAN LPP RRI - Rahayu, Dwi Nur; Sari, Imelda (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
This study was conducted on employees of the News Center of the Public Broadcasting Institution Radio Republik Indonesia (LPP RRI), which plays a strategic role in delivering information to the public. The purpose of this study was to examine the effect of leadership style and work facilities on employee job satisfaction. This research employed a quantitative approach with an associative research design. Data were collected through the distribution of questionnaires to 55 respondents selected using the Slovin formula from a total population of 112 employees. The data were analyzed using multiple linear regression with the assistance of SPSS version 29. The results show that leadership style has a significant effect on job satisfaction with a t-value of 5.780, while work facilities also have a significant effect with a t-value of 3.488. Simultaneously, both variables significantly affect job satisfaction with an F-value of 48.164. These findings confirm that improvements in leadership quality and the provision of adequate work facilities can have a positive impact on employee job satisfaction in the News Center of LPP RRI.